ANALISIS PENGELOLAAN ALOKASI DANA DESA (ADD) TERHADAP PEMBERDAYAAN MASYARAKAT DI TINJAU DARI PERSPEKTIF EKONOMI ISLAM DI DESA JABAL NUR KECAMATAN KODEOHA KABUPATEN KOLAKA UTARA - Hasmiana Hasmiana; Hartono Hartono; Moch Abd Azis (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Village Fund Allocation is funds sourced from the State Revenue and Expenditure Budget allocated to Villages which are transferred through the Regency / City Regional Revenue and Expenditure Budget which was rolled out from 2015 with the aim of financing governance, implementation of development, guidance and community empowerment. Village Funds have an important role in improving the economy of rural communities, by utilizing and allocating them effectively and efficiently.The purpose of this research is first, to find out how village funds are managed in community empowerment aimed at improving the village economy. Second, how are the efforts made by the village government in increasing community empowerment. Third, to find out how village funds are managed from an Islamic economic perspective.This research is a qualitative research with descriptive research type. The research procedure carried out included the observation, interview and documentation stages related to the formulation of the problem in this study. The instruments used in research were interview guidelines, observation guidelines, as well as photos and voice recorders which were documentation media. The data analysis techniques used are data reduction, data presentation, drawing conclusions, and testing the validity of the data.The results showed that the management of village funds in Jabal Nur village, Kodeoha District, North Kolaka Regency, was based on existing technical guidelines so that community empowerment from 2015-2019 began to increase in terms of development and in community empowerment itself was quite effective.The policies implemented by the government in carrying out their duties are based on the basic values ​​of Islamic economics, namely: ownership, balance and justice. The government collaborates with existing institutions in the village, and decisions taken by the government are joint decisions in the Village Development Planning Consultation (Musrenbangdes). The management of village funds is in accordance with sharia